Estudo da permeabilidade intestinal em pacientes com tuberculose pulmonar ativa - Pinheiro, Valéria Góes Ferreira (2003)
Subtherapeutic antimycobacterial drugs levels have been observed during treatment of patients with tuberculosis and in HIV coinfected. It may facilitate the development of M. tuberculosis resistant strains. Malabsorption may be one of the underlyne cause. It has been documented in tuberculosis patients associated to malnutrition, alchoolics, diabetes, AIDS and gastrointestinal symptoms. Intestinal permeability studies have been conducted in order to evaluate the intestinal function in some diseases but are scant in tuberculosis. Lactulose / manitol ratio in urine a widely used measure of malabsorption and intestinal permeability may be useful to assesss the drug absorption area in tuberculosis. In order to study the intestinal permeability in tuberculosis, we conducted in a pilot study 40 patients and 28 healthy volunteers, using the urinary excretion of ingested lactulose and manitol as respective markers of barrier disruption and overall villous surface area. The Maracanaú Hospital in Fortaleza-CE, was choosen and the data were collected in 2001. Eigthteen patients receiving 600 mg rifampicin (R) and 400 mg isoniazid (H) were evaluated through venous blood analysis obtained at 2 hours after directly observed ingestion. The serum samples were analysed by HPLC at the Infectious Disease Pharmacokinetics Laboratory / National Jewish Center / Denver, USA. Nutritional status by body mass index (BMI) and serum drug levels were correlated with intestinal permeability data. M. tuberculosis isolates from 20 clinical specimens were tested to drug susceptibility by standard proportion method (APM ) using Lowestein-Jensen medium. Forty-one patients (30 M, 11 F) were studied. Fifty nine per cent (24) patients were malnourish (BMI<18,5 kg/m2); 22% (9) were severely malnourish (BMI<16 kg/m2). The urinary excretion of mannitol (mean ± standard deviation) showed a significant decrease p < 0,001 in patients (9,52 ± 5,70) compared to controls (20,14 ± 10,84). The excretion of lactulose was significant increased p < 0,05 in patients (0,59 ± 1,79), than controls (0,52 ± 0,47) and the L/M ratio shown consistent increased (0,05 ± 0,10) in patients compared to controls (0,029 ± 0,0,02) p > 0,05. Considering the reported target range for R (8-24 mcg/mL ) and H (3-6 mcg/mL) we observed that 2-h serum levels were below the lower limit for R and H in 88,8% (16/18) patients. Forty four per cent ( 8/18) of patients had reduced levels for the two drugs. Analysing single drugs we documented that 66,7% (12/18) patients had levels below the target limit for R (mean R =6,47 mcg/mL) and 72,2% (13/18) for H (mean H =2,17mcg/mL). Concerning to M. tuberculosis susceptibility profile in sputum culture, we observed 20% (4/20) multidrug resistants strains (3 for R + H and 1 for all drugs). Ten per cent (2/20) were resistant only for H and 70% (14/20) strains were sensitive. These results suggests an important decrease in the funcional absorptive surface of the intestine and damage of the intestine in patients studied. The data are consistent with reduced antituberculosis drugs bioavailability and compromissed nutritional status of these patients. The preliminary results indicate the necessity of new approaches to accurate portrait of drugs bioavailability in tuberculosis patients.